2000
DOI: 10.1038/sj.ejcn.1601092
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a dietary record routine in geriatric patients using doubly labelled water

Abstract: Objective: To validate a 7-day estimated dietary record routine with standardized portion sizes and household measuring in a clinical setting with the doubly labelled water (DLW) method as the reference method. Design: Energy expenditure was measured with deuterium ( 2 H) and oxygen-18 ( 18 O), and water loss was estimated by 2 H dilution as part of the DLW measurements. Energy and water intake was measured with a 7 day dietary record. Setting: Five nursing home wards in Sweden. Subjects: Thirty-one geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
(34 reference statements)
2
14
1
Order By: Relevance
“…Bjornsdottir et al [3] reported significant, high correlations between a food chart and weighed food records for daily energy (r ¼ 0.922, p < 0.001) and protein (r ¼ 0.896, p < 0.001) intakes using a larger sample size (n ¼ 73) and trained staff. Lorefalt et al [5] and Persson et al [6] had similar sample sizes to our study, yet also found higher correlations (r ¼ 0.97, p < 0.001; r ¼ 0.81, p < 0.001, respectively) for daily energy intake with additional staff training. Masson et al [16] suggested that an acceptable level of agreement occurs when 10% of test data is grossly misclassified.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Bjornsdottir et al [3] reported significant, high correlations between a food chart and weighed food records for daily energy (r ¼ 0.922, p < 0.001) and protein (r ¼ 0.896, p < 0.001) intakes using a larger sample size (n ¼ 73) and trained staff. Lorefalt et al [5] and Persson et al [6] had similar sample sizes to our study, yet also found higher correlations (r ¼ 0.97, p < 0.001; r ¼ 0.81, p < 0.001, respectively) for daily energy intake with additional staff training. Masson et al [16] suggested that an acceptable level of agreement occurs when 10% of test data is grossly misclassified.…”
Section: Discussionsupporting
confidence: 83%
“…The FCRR and FCSI therefore had an unacceptable level of agreement at most meals and mid-meals. Yet Persson et al [6] had trained staff and found acceptable agreement using an intake estimation tool as nil patients were grossly misclassified by tertiles. The limits of agreement for both test methods were wide for energy and protein intakes at all meals and mid-meals (À497eþ552 kCal, À27eþ36 g protein), indicating poor agreement at the individual level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean knee height for the participants was 49 cm (range 47-56), corresponding to a calculated mean stature of 156 cm (range 149-175) and the mean BMI, 26 kg/m 2 , was within the normal range (24)(25)(26)(27)(28)(29) suggested for old people (23). Three people had a BMI < 23 and two >30 kg/m 2 .…”
Section: Study Populationmentioning
confidence: 85%
“…A record of BW, body height, bowel movements frequency (BMF), bowel movements consistency (BMC), dietary intake (24) and physical activity was kept during a 14-day period prior to the intervention. A 7-day dietary and activity registration and the assessments of the BW were repeated 3 times during the intervention (at baseline, and after 3 and 6 months).…”
Section: Study Proceduresmentioning
confidence: 99%